Réponses

2014-04-07T17:29:04+02:00
8-3x=6
-3x=6-8
-3x=-2
x=-2/-3=2/3

5x-3=-2x+5
5x+2x=3+5
7x=8
x=8/7

2/7x=5
x=5/(2/7)

6-(4x-3)=5(2-3x)

6-4x+3=10-15x
-4x+15x=10-6-3
11x=1
x=1/11
Meilleure réponse !
2014-04-07T17:34:41+02:00
Salut :)

8 - 3x = 6
-3x = 6 - 8
-3x = -2
x = -2/-3
x = 2/3

5x - 3 = -2x + 5
5x - 3 + 2x = 5
7x - 3 = 5
7x = 5 + 3
7x = 8
x = 8/7

2/7x = 5
x = 5 / 2/7
x = 5 x 7/2
x = 35/2

6 - (4x - 3) = 5(2 - 3x)
6 - 4x + 3 = 5 x 2 + 5 x (-3x)
9 - 4x = 10 - 15x
9 - 4x + 15x = 10
9 + 11x = 10
11x = 10 - 9
11x = 1
x = 1/11

J'espère t'avoir aidé(e) ! :)